Relational Coherence in Educating Generation Alpha: Digital Exposure, Adult Guidance, and Home-School Coordination in Indonesian Early Childhood Education - R. Slate, John; Vinodhen, Vanessa; Putri Amanah, Adinda; Xolile Ntshangase, Mohammed (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2026)
This study examines how adults involved in early childhood education in Indonesia understand Generation Alpha, respond to children’s digital exposure, and identify challenges in guiding children across home and school. Rather than treating Generation Alpha simply as a technologically fluent cohort, the study approaches digital childhood as a developmental and relational condition shaped by adult guidance, family routines, teacher authority, and home-school coordination. A small-scale interpretive qualitative design was employed, with data collected through open-ended written responses from three purposively selected adult participants who were directly involved in raising or educating young children. The responses were analyzed thematically to identify recurring patterns in participants’ understandings, strategies, concerns, and perceived barriers. The findings show that participants initially defined Generation Alpha through birth cohort and digital proximity. Their educational responses emphasized gadget supervision, personal attention, skills development, and holistic guidance. Digital exposure was associated with concerns about discipline, reduced social interaction, and communication development, although these concerns should be understood as adult perceptions rather than causal evidence. The most prominent pattern was relational: participants repeatedly linked educational difficulties to limited parental involvement, weak trust in teachers, and insufficient cooperation between home and school. The study contributes to global discussions on Generation Alpha by shifting attention from digital competence alone to relational coherence. It suggests that early childhood education in digitally saturated environments depends not only on how families and schools manage technology, but also on how adults build shared expectations, consistent guidance, and trustworthy relationships that support children’s learning, communication, and development.